Using the penalized splines regression method to estimate the logistic model and using a practical application (Journal of the College of Basic Education, 2022)
This paper focused on a method for non-parametric in estimating the binary response logistic regression model, which is the method of regression of the slides (P-Spline), by applying practical data on the ground that represents the change in stock prices and the current value of the Babylon Hotel in the Iraq Stock Exchange. Finance, and for three sizes of samples (the first sample size is 45) (the second sample size 72) (the third sample size 110), it was concluded that the preference in the estimation method (P-Spline) was the sample size (110), in order to obtain the lowest value With an MSE standard.